The Effect of “Numbered Heads Together” vs “Three Minutes Review” on Students’ Vocabulary Mastery - Chubbi Millatina Rokhuma (Cakrawala: Jurnal Pendidikan, 2017)
The aim of this study is to investigate the effect of Numbered Heads Together and Three Minutes Review techniques on students’ vocabulary mastery. It used quantitative approach with factorial design. It involved the seventh graders of Simbang Wetan Islamic Junior High School Pekalongan that were chosen through purposive sampling. Class 7A that consisted of 25 students was considered as the experimental group, and they were taught by using Numbered Heads Together. On the other hand, class 7B that consisted of 27 students was considered as the control group, and they were taught by using Three Minutes Review. The methods of data collection of this study were observation, questionnaire, and test. Based on the calculation of the research result, it showed that Ftable = 4.26 and Fcount = 17.39. Because Fcount > Ftable, so Ho is rejected and Ha is accepted. It can be concluded that there is significant difference between the post-test score of experimental group and control group. In other words, Numbered Heads Together is more effective than Three Minutes Review in teaching vocabulary for high and low achievers.